2006
DOI: 10.1007/s11373-006-9091-9
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of GFAP and αB-crystallin after thermal stress in C6 glioma cell line

Abstract: SummarySome intermediate filament (IF) proteins expressed in the development of glia include nestin, vimentin, and glial fibrillary acidic protein (GFAP). However, GFAP is the major intermediate filament protein of mature astrocytes. To determine the organization of GFAP in glial cells, rat GFAP cDNA tagged with enhanced green fluorescent protein (EGFP) was transfected into the rat C6 glioma cell line. After selection, two stable C6-EGFP-GFAP cell lines were established. Stable C6-EGFP-GFAP cell lines with or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…αB-crystallin is well known as a binding partner for type III intermediate filaments, including vimentin [37], desmin [38], and GFAP [39]. Studies in both C6 cells and in primary astrocytes demonstrate that αB-crystallin can influence GFAP integration into the cytoskeletal network, both by regulating normal assembly and by assisting in recovery from stress [37,40]. …”
Section: Discussionmentioning
confidence: 99%
“…αB-crystallin is well known as a binding partner for type III intermediate filaments, including vimentin [37], desmin [38], and GFAP [39]. Studies in both C6 cells and in primary astrocytes demonstrate that αB-crystallin can influence GFAP integration into the cytoskeletal network, both by regulating normal assembly and by assisting in recovery from stress [37,40]. …”
Section: Discussionmentioning
confidence: 99%
“…Several reports indicated that a-crystallin may interact with different cellular components, like cytoplasmic membrane, cytoskeletal elements, and mediators of cell death (Cobb and Petrash 2000;Kamradt et al 2001;Liu et al 2004;Mao et al 2004;Li et al 2005). As a result of these interactions, a-crystallin maintains the stability of the cellular structures and inhibits the activity of caspases to reduce the stress-induced damage (Nicholl and Quinlan 1994;Wang and Spector 1996;Djabali et al 1997;Tseng et al 2006;Xi et al 2006).…”
Section: )mentioning
confidence: 99%
“…As a result of these interactions, α‐crystallin maintains the stability of the cellular structures and inhibits the activity of caspases to reduce the stress‐induced damage (Nicholl and Quinlan 1994; Wang and Spector 1996; Djabali et al. 1997; Tseng et al. 2006; Xi et al.…”
mentioning
confidence: 99%
“…The GFAP gene is first expressed as astrocytes mature and in the adult is strongly up-regulated in response to central nervous system damage. It has been suggested that RFs may represent a metabolite of upregulation of GFAP in response to stress [13,18,23]. The abundant RFs seen in association with our case of CD may represent a dysregulation of α-B-crystallin aggregating in association with GFAP or be secondary to the severity of the CD that produces a dys/up-regulation of GFAP to levels sufficient to induce RFs and localized leukodystrophy, in some cases, due to astrocytic dysfunction [18].…”
Section: Discussionmentioning
confidence: 62%